COMPARATIVE STUDY OF SOME HEAVY METALS CONTENT IN WILD AND CULTURED CATFISH (Clarias gariepinusis) SOLD IN SAMARU- ZARIA, NIGERIA - Israila Yashim, Zakka; Abdullahi, Y. F. (FUDMA JOURNAL OF SCIENCES, 2023)
This study is to assess the level of some heavy metals in samples of wild and cultured catfish (Clarias gariepinusis) regularly consumed, therefore, the need to ascertain the safety of the consumption of this fish. Fresh samples of the wild and the cultured Clarias fish of different sizes were purchased from different locations in Samaru – Zaria, Nigeria. The fish samples were digested with a mixture of 20 cm3 concentrated nitric acid and 5 cm3perchloric acid (ratio 4:1). The concentrations of lead, copper, chromium, cadmium and Zinc were determined using atomic absorption spectrophotometer (AAS). The results obtained indicated that in both wild and cultured Clarias gariepinusis, the concentration of Zn > Cr > Cu > Pb > Cd. The concentrations of all the heavy metals determined in the various sizes of wild Clarias gariepinusis samples were higher than the corresponding cultured Clarias fish. In both wild and the cultured Clarias fish the concentrations of Cd, Pb and Cr were found to be in the order of: small size > medium size > large size, but for Cu and Zn there were variations in concentrations. In wild Clarias fish the concentrations of Cd, Pb and Cr were found to be higher than the permissive limits set by FAO/WHO, while in cultured fish only Cr concentration was higher than the permissive limit.  Though the contents of heavy metals determined in this study have a great health implication on human, aquaculture and fisheries activities be encouraged.
Keywords: Clarias gariepinusis; Heavy metals; Human Health; Toxicity